PERSEPSI MAHASISWA STKIP WIDYA YUWANA TERHADAP HUBUNGAN ANTARA PENERAPAN METODE BELAJAR KONTEKSTUAL DAN INDEKS PRESTASI BELAJAR - Siribentuk, Kristiani Putri Gijai; Wilhelmus, Ola Rongan (CREDENDUM: Jurnal Pendidikan Agama, 2019)
This study aims to analyze the perceptions of STKIP Widya Yuwana students regarding the relationship between the application of contextual learning methods and their learning achievement index (GPA). The research uses a quantitative approach with a correlational descriptive design, involving a sample of students as respondents. Data will be collected through surveys or questionnaires to measure students' perceptions of the contextual learning method and their academic performance. The study will explore how students perceive the impact of contextual learning on their GPA, identifying factors that contribute to the effectiveness of this teaching method in improving academic success. The findings are expected to provide valuable insights for educators on how to optimize teaching methods to improve student achievement, thereby contributing to the development of more effective pedagogical strategies in higher education institutions.